2014
DOI: 10.1302/2046-3758.311.2000207
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous cultured growth plate chondrocyte transplantation in the treatment of physeal injury in rabbits

Abstract: ObjectivesThe aim of this experimental study on New Zealand’s white rabbits was to investigate the transplantation of autogenous growth plate cells in order to treat the injured growth plate. They were assessed in terms of measurements of radiological tibial varus and histological characteristics. MethodsAn experimental model of plate growth medial partial resection of the tibia in 14 New Zealand white rabbits was created. During this surgical procedure the plate growth cells were collected and cultured. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…The growth plate is a cartilage between the metaphyseal and epiphyseal bone at the ends of the longitudinal bones [ 20 ]. Chondrocytes in the growth plate control longitudinal growth via proliferation, hypertrophy, apoptosis, cartilage matrix synthesis, mineralization, and vascularization [ 21 ]. The growth plate can be divided into the resting, proliferative, and hypertrophic zones according to the distinctive histological chondrocyte differentiation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth plate is a cartilage between the metaphyseal and epiphyseal bone at the ends of the longitudinal bones [ 20 ]. Chondrocytes in the growth plate control longitudinal growth via proliferation, hypertrophy, apoptosis, cartilage matrix synthesis, mineralization, and vascularization [ 21 ]. The growth plate can be divided into the resting, proliferative, and hypertrophic zones according to the distinctive histological chondrocyte differentiation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes can also be obtained from different compartments in autograft or allograft. In an autologous chondrocyte experiment, Tomaszewski et al (2014) resected the medial part of the proximal tibia GP in rabbits and then implanted it in the GP defects. Histological and radiological results demonstrated that implanting of autologous chondrocytes significantly prevented the bone bridge formation and growth arrest.…”
Section: Cartilage Tissue Engineering For Gp Injuriesmentioning
confidence: 99%
“…77 Chondrocytes from the growth plate may be isolated, cultured and expanded in vitro and used to prevent bone bridge formation. 78,79 However, no report has used autologous chondrocytes from the growth plate for cartilage repair, primarily due to potential severe complications.…”
Section: Autologous Cartilage/costa-derived Chondrocyte Implantationmentioning
confidence: 99%